2007
DOI: 10.1111/j.1559-1816.2008.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Right‐Wing Authoritarianism in Relation to Proposed Judicial Action, Electromyographic Response, and Affective Attitudes Toward a Schizophrenic Mother

Abstract: Student participants who were high vs. low on Altemeyer's (1996) Right‐Wing Authoritarianism (RWA) scale read background information and observed a videotaped interview concerning a schizophrenic woman who ostensibly killed her 2 young children in response to what she perceived as divine command. The woman now was functioning normally in response to medical treatment. High RWAs recommended harsher sentencing and expressed less sympathy than did low RWAs. High RWAs also evinced more facial electromyographic act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…These associations provide additional evidence for Suziedelis and Lorr's (1973) argument that conservatism represents the same construct as right-wing authoritarianism. While politically conservative jurors in the present study tended to be more punitive in their beliefs, they did not exhibit significant tendencies to actually sentence more harshly, contradicting prior findings regarding juror behavior (Bray & Noble, 1978;Fodor et al, 2008;Mitchell & Byrne, 1973). Despite minor limitations in the present study, it presents findings of importance in the courtroom.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These associations provide additional evidence for Suziedelis and Lorr's (1973) argument that conservatism represents the same construct as right-wing authoritarianism. While politically conservative jurors in the present study tended to be more punitive in their beliefs, they did not exhibit significant tendencies to actually sentence more harshly, contradicting prior findings regarding juror behavior (Bray & Noble, 1978;Fodor et al, 2008;Mitchell & Byrne, 1973). Despite minor limitations in the present study, it presents findings of importance in the courtroom.…”
Section: Discussioncontrasting
confidence: 55%
“…High authoritarian jurors have been found more likely to see offenders as criminally responsible, more deserving of punishment, and less likely to have sympathy for an offender (Feather, 1996), and thus such jurors tend to give more guilty verdicts and sentence more harshly (Bray & Noble, 1978;Fodor, Wick, Hartsen, & Preve, 2008;Mitchell & Byrne, 1973). Fodor and colleagues (2008) found that high authoritarian jurors reported less sympathy specifically for mentally ill offenders.…”
Section: Conservative Political Attitudesmentioning
confidence: 99%
“…In regard to MH stigma, self-reported conservatism has been linked to attributing mental illness with ‘bad character’ (Watson, Corrigan, & Angell, 2005) and supporting less government funding for MH services (Barry & McGinty, 2014). RWA has been linked to harsher sentencing toward a hypothetical person with mental illness (Fodor, Wick, Hartsen, & Preve, 2008), lower evaluations toward a hypothetical job candidate with schizophrenia (Fodor, 2006) and negative attitudes toward MH services (Furr, Usui, & Hines-Martin, 2003). Recent studies have demonstrated that RWA is a consistent predictor of the endorsement of negative stereotypes and intended social distance toward people with mental illness, even when controlling for other consistent individual-level predictors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have looked at the relationship between RWA and mental health stigma, the existing research suggests that RWA is associated with greater stigma. Fodor, Wick, Hartsen, and Preve (2008), for example, found that individuals with High RWA recommended harsher sentencing and showed less empathy toward a hypothetical person with schizophrenia than other participants. In a similar study, Fodor (2006) found that individuals with High RWA gave lower evaluations and expressed less comfort with a hypothetical job candidate with schizophrenia in comparison with a 'Low RWA' group.…”
mentioning
confidence: 99%